2018
DOI: 10.1371/journal.pone.0203050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geometry and topography on Min-protein dynamics

Abstract: In the rod-shaped bacterium Escherichia coli, the center is selected by the Min-proteins as the site of cell division. To this end, the proteins periodically translocate between the two cell poles, where they suppress assembly of the cell division machinery. Ample evidence notably obtained from in vitro reconstitution experiments suggests that the oscillatory pattern results from self-organization of the proteins MinD and MinE in presence of a membrane. A mechanism built on cooperative membrane attachment of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
(113 reference statements)
1
12
0
Order By: Relevance
“…The formation of the MinDE wave patterns depends on the protein concentration, the molar ratio between MinD and MinE, and the geometrical confinement in which the wave patterns are reconstituted (7)(8)(9)(10)(11)(12). Along with the experimental works, a series of numerical models have been reported to simulate the formation of the Min protein waves based on the reaction-diffusion theory (5,(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the MinDE wave patterns depends on the protein concentration, the molar ratio between MinD and MinE, and the geometrical confinement in which the wave patterns are reconstituted (7)(8)(9)(10)(11)(12). Along with the experimental works, a series of numerical models have been reported to simulate the formation of the Min protein waves based on the reaction-diffusion theory (5,(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, these studies explicitly accounted for the dimension perpendicular to the membrane [11]. Although similar patterns were obtained in two-and in three-dimensional calculations [68], quite different parameter values were needed in both cases to obtain patterns with the same characteristic length and time scales. As an aside, let us also note that, for the time being, no non-trivial limit has been identified in which the three-dimensional description of cooperative binding can formally be replaced by a two-dimensional description.…”
Section: (A) Open Geometriesmentioning
confidence: 68%
“…However, the formation of Min-protein surface waves per se does not require the presence of cardiolipin [64,66]. Furthermore, experiments on aberrantly shaped E. coli, which revealed a preferential localization to regions of high curvature [17,18], and experiments on topographically structured surfaces [71], which might suggest an essential role for membrane curvature on the Min-protein patterns, can all be reproduced by mechanisms that do not account for differences in MinD binding affinities to membranes of different curvatures [11,17,68]. understanding of the Min-protein self-organization, the processes of MinD and MinE attachment to and detachment from the membrane need to be characterized in more detail and the corresponding rate constants need to be measured.…”
Section: (A) Open Geometriesmentioning
confidence: 99%
“…Recent theoretical analysis of the MinDE system has reported that the pattern formation of MinDE heavily depends on the surface to volume coupling, suggestive of even richer and partly unexplored MinDE pattern formation. 77,78 In addition to their role as the spatial indicators of the E. coli midcell, MinDE waves have also been shown to position and transport biologically unrelated membrane-bound molecules by non-specific interactions. 67 The directionality of MinDE waves on rods demonstrated here could be exploited to specifically guide MinDE waves and thereby transport arbitrary molecules on membrane surfaces to a desired location.…”
Section: Dynamic Protein Patterns On 3d Microstructuresmentioning
confidence: 99%